Boosting Political Trust with Direct Democracy? The Case of the Finnish Citizens’ Initiative - Christensen, Henrik Serup (2019)
Complementing representative democracy with direct-democratic instruments is perceived to boost levels of political trust. This was why Finland in 2012 introduced an agenda initiative, which gives citizens the right to propose legislation and thereby provides citizens a say between elections. However, it remains unclear whether involvement in such mechanisms helps restore political trust and what factors shape developments in political trust during involvement. This article contributes to this research agenda by examining how using the Finnish agenda initiative affected developments in political trust. The study uses two surveys to determine developments in political trust: a four-wave panel survey (n = 809 - 1419) and a cross-sectional survey (n = 481) where the perceived change method is used. The results suggest that using the citizens’ initiative did not necessarily cause positive developments in political trust. Nevertheless, positive developments in political trust occurred when users achieved their intended aim and/or the process was seen as fair, which shows that direct-democratic instruments can increase levels of political trust under some circumstances.